2021
DOI: 10.2174/2666082217666211207102342
|View full text |Cite
|
Sign up to set email alerts
|

Association between Structural Determinants of Health and Posttraumatic Stress Symptoms during the COVID-19 Pandemic

Abstract: Background: Psychological problems, such as post-traumatic stress symptoms (PTSS), are among the most important complications associated with the COVID-19 pandemic in people. Studying the social determinants of health (SDH) and its impact on the populations during the crisis will help governments deal better with health emergencies so that every person can have an equal opportunity to stay healthy. Objective: To determine what factors affect PTSS, we conducted a study to investigate the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…A study on refugees in Bangladesh also showed a negative impact of the COVID-19 pandemic on their quality of life [ 44 ]. The mean PTSD of Afghan refugees in our study was higher than a study of Iranian pupations [ 45 ], which may be because of a higher level of stress, anxiety, depression, and other immigration problems in Afghan refugees. A qualitative study in Iran illustrated that Afghan refugees, especially women, are very vulnerable to COVID-19.…”
Section: Discussioncontrasting
confidence: 84%
“…A study on refugees in Bangladesh also showed a negative impact of the COVID-19 pandemic on their quality of life [ 44 ]. The mean PTSD of Afghan refugees in our study was higher than a study of Iranian pupations [ 45 ], which may be because of a higher level of stress, anxiety, depression, and other immigration problems in Afghan refugees. A qualitative study in Iran illustrated that Afghan refugees, especially women, are very vulnerable to COVID-19.…”
Section: Discussioncontrasting
confidence: 84%
“…In line with our study, Fernandez-de-Las-Penas found that women are more likely to develop symptoms of COVID-19 8 months after contracting the virus than men (Fernández-de-Las-Peñas et al, 2022). In addition, many studies have reported gender as a risk factor associated with post-COVID complications and greater stress after the disease (Iqbal et al, 2021; Mahmoodi et al, 2021). Another study revealed that gender predicts COVID-19 complications such as dyspnea, fatigue, chest pain, and palpitation (Pelà et al, 2022; Yong, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the consequences, people adopt avoidant behaviours that may disrupt the overall quality of their daily functioning [ 27 ]. Studies show that the complications and mortality caused by this disease are higher in people with chronic diseases, which induces or exacerbates fear and anxiety in them [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%